ANALISA PENGARUH PENGGUNAAN PENGAKU VERTIKAL TERHADAP PERILAKUTEKUK TORSI LATERAL PADA BALOK BAJA BERBENTUK H DI BAWAH PENGARUH MOMEN KURVATUR GANDA DENGAN MENGGUNAKAN ABAQUS - John Thedy (Jurnal Teknik Sipil USU, 2014)
Abstract This report is made to give an illustration and recommendation of effective stiffener attachment on H-shaped steel beam in building construction which converts buckling mode from lateral torsional buckling to local buckling, when the buckling mode changes, the value of critical moment was analyzed. The buckling analysis based on elastic analysis and the critical moment value was count using finite element method through computer software ABAQUS. Eleven beam models with different section will be used, each section is attached by various spacing of stiffener, and each section of beam will be given three different flange’s support condition which is bare beam, beam with lateral support and beam with continous lateral torsional support to represent the effect of plate above beam. In result, it will be seen the effect from parameter Ix/Iy, various spacing of stiffener, and flange support condition. From all those parameter, this report will produce an equation that is recommended to find the effective spacing of stiffener. Key word: Beam, Steel, Lateral torsional buckling, stiffener, ABAQUS